Longleaf Pine Regeneration - Chris Demers; Alan Long; Patrick Minogue (EDIS)
Revised! SS-FOR-13, a 8-page fact sheet by Chris Demers, Alan Long, and Patrick Minogue, provides landowners with long-term, multiple-use resource management objectives with strategies for artificial and natural regeneration of this insect-, disease-, and fire-resistant species. Includes references. Published by the UF Department of School of Forest Resources and Conservation, November 2010.